QR Code as a Google Spreadsheet-Based AKM Supporting Application - Khilmatuz Zuhria1; Fitria Nur Hasanah (Journal for Technology and Science, 2024)
An important supporting tool to support AKM is the QR Code (Quick Response Code). QR Code is much more practical and has many advantages over barcodes. This study aims to develop a QR Code supporting tool and determine the feasibility of a QR Code supporting tool as a Google Spreadsheet-Based AKM Supporting Application in Yapenas Gempol Vocational School. This type of research uses Research and Development (R&D), the R&D method used is the ADDIE development model (Analysis, Design, Development or Production, Implementation or Delivery and Evaluations). The research subject is the teacher or the AKM examination committee. The research instrument used was interviews to determine the feasibility of the supporting tools that had been developed. These supporting tools will be validated by 2 validators, namely media experts and content experts. Supporting tools have been validated by media experts and content experts with a percentage of media experts which include media expert validation indicators with navigation indicators of 93%, writing (text) 95%, display 89%, and media presentation 92%. For content expert validation with a display indicator of 91%, and content of 93%. The results of the trial results were obtained from the media display aspect, and the media effectiveness aspect obtained an average of 92% with very high eligibility criteria so that it can be concluded that the supporting tools for supporting AKM can be used to process AKM activities in the next school year and can be used for other assessment activities.